Sosialisasi Keamanan Cyber Kepada Siswa Sekolah Paket C : Menjaga data dan Privasi - Maulana, Fajar; Hendra, Yomei; Thoriq, Muhammad; Eirlangga, Yofhanda Septi; Syaputra, Aldo Eko; Manurung, Kiki Hariani; Hayati , Nova; Mufid, Muhammad Fauzan (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2025)
Community service is one of the obligations of lecturers in implementing the Tri Dharma of Higher Education, aimed at assisting and supporting activities within the community. One such activity is carried out at PKBM Suka Maju Sejahtera (SMS) Padang, a non-formal educational institution focusing on educating disadvantaged communities through Programs A, B, and C. In the increasingly digital era, students face various challenges related to cyber security, such as threats to personal data and a lack of understanding about privacy protection in the online world. The low awareness among students about these threats increases the risk of misuse of personal information. Therefore, the community service conducted by lecturers from the Information Systems Study Program of Universitas Adzkia aims to provide students of the PKBM SMS Padang Program C with knowledge about cyber security, data protection, and privacy. This activity is expected to help students become more prudent in using the internet and understand how to effectively protect their personal information.